Development and production of curly lettuce using cultures for lateral shading - Pinto, Antônio Alves; Santana, Laudeline Dantas; Camara, Felipe Thomaz da; Rodrigues, Wíctor Állyson Dias; Costa, Maria Nágila Ferreira da; Penha Filho, Nerton da (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2017)
Vegetables cultivation in agroecological system has grown in last years, this is because society has required more quality of products they consume. With this view, the objective of this work was to evaluate the development and production of two lettuce cultivars, conducted in organic system, using two cultures for lateral shading. This work was realized in the experimental area of the Center of Agricultural Biodiversity Sciences of the Federal University of Cariri. The transplanting of seedlings was realized in 19 days after seeding in tray with 128 cells, in a spacing 0,3 x 0,3 m. It was evaluated the diameter of shoot and stem, number of leaves, length and width of largest leaf, stem and root, plus hole plant mass, leaves, stem and root. The lettuce Monica presented better productive result than Grand Rapids. Cultures used like shading didn’t influenced in lettuce production.